New evidence for SPX2 in regulating the brain-pituitary reproductive axis of half-smooth tongue sole (Cynoglossus semilaevis) - Wang, Bin; Wang, Kaijie; Tian, Zhenfang; Cui, Aijun; Liu, Xin; Jin, Zhixin; Liu, Xuezhou; Jiang, Yan; Xu, Yongjiang (Frontiers in Endocrinology, 2022)
Spexin (SPX) is an evolutionarily conserved neuropeptide, which was first identified in human proteome by data mining. Two orthologs (SPX1 and SPX2) are present in some non-mammalian species, including teleosts. It has been demonstrated that SPX1 is involved in reproduction and food intake, whereas the functional role of SPX2 is still absent in any vertebrate. The aim of the current study was to evaluate the actions of intraperitoneal injection of endogenous SPX2 peptide on the expression levels of some key reproductive genes of the brain-pituitary axis in half-smooth tongue sole. Our data showed an inhibitory action of SPX2 on brain gnih, spx1, tac3 and pituitary gthα, lhβ mRNA levels. However, SPX2 had no significant effect on brain gnihr, gnrh2, gnrh3, kiss2, kiss2r, spx2 expression or pituitary gh expression. On the other hand, SPX2 induced an increase in pituitary fshβ expression. Taken together, our results provide initial evidence for the involvement of SPX2 in the regulation of reproduction in vertebrates, which is in accordance with previous studies on SPX1.